Sistem Pendidikan Karakter di SD Alam Islami Elkisi dalam Perspektif Kitab Ta’lim Muta’allim - Nur Qomariyah; Ika Agustin Adityawati (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2022)
Character education is a effort to instill positive values for student to become good humans in all. Character education is expected to be amoral-social crisis that is happening in Indonesia. Responding to this, SD Alam Islami eLKISI made character education main program in forming the character of students. The purpose of this reseach is 1) To describe a designated character education system in SD Alam Islami eLKISI. 2) To describe and analyze the values of character education in SD Alam Islami eLKISI perspective of the Ta’lim Muta’allim book. This type of reseach uses a qualitative approach The methods of observation, interviews and documentation. The result of this study are 1) the character education system in SD Alam Islami eLKISI which is determinated based on three things, namely school programs that can indirectly shape the positive character of students, binding rule and sanction applied and strategies of implementing character education using learning, exemplary habituation, the existence a liaison book as well briefing and evaluation. 2) the values set in the programs and activities include religious, honest, disciplined, fond of reading, caring, environmental, social care and responsibility in accordance with the view of the book Ta’lim Muta’allim.